2022
DOI: 10.1136/bmjopen-2022-062013
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of kinesiophobia between self-efficacy and physical activity levels in post-CABG patients: protocol for a prospective, multicentre, cross-sectional study in China

Abstract: IntroductionPhysical activity (PA) can improve cardiac function, exercise capacity, and quality of life, in addition to reducing mortality by 20%–30% and preventing the recurrence of adverse cardiovascular events in patients following coronary artery bypass graft (CABG). However, PA levels are low in patients after CABG. This study intends to explore the mediating effect of kinesiophobia between self-efficacy and PA levels in patients following CABG.Methods and analysisThe proposed study constitutes a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…According to the above results, kinesiophobia leads to maladaptive avoidance behavior, causing adverse health consequences such as physical inactivity. A previous study also confirmed that kinesiophobia was an essential mediator of PA in patients with cardiovascular disease [37], which was similar to our study results. These findings suggested that both CHF-related symptoms and kinesiophobia need to be identified and addressed as early as possible to avoid later deterioration of postdischarge transition PA.…”
Section: The Mediating Effect Of Kinesiophobia On the Relationship Be...supporting
confidence: 93%
“…According to the above results, kinesiophobia leads to maladaptive avoidance behavior, causing adverse health consequences such as physical inactivity. A previous study also confirmed that kinesiophobia was an essential mediator of PA in patients with cardiovascular disease [37], which was similar to our study results. These findings suggested that both CHF-related symptoms and kinesiophobia need to be identified and addressed as early as possible to avoid later deterioration of postdischarge transition PA.…”
Section: The Mediating Effect Of Kinesiophobia On the Relationship Be...supporting
confidence: 93%
“…On the contrary, patients with low self-efficacy are more likely to feel frustrated when faced with difficulties and may choose to avoid or give up. Wang Yaxin [30] found that the lower the self-efficacy of patients with first-episode acute myocardial infarction, the higher their level of fear of movement, which is consistent with the results of other domestic studies [32][33][34] . Foreign studies [35] also emphasize the need to adopt intervention strategies to enhance the self-efficacy of patients with coronary heart disease to improve compliance with cardiac rehabilitation exercises.…”
Section: Self-efficacysupporting
confidence: 77%
“…In this study, kinesiophobia mediated the relationship between CHF-related symptoms and PA, implying that the association between CHF-related symptoms and PA was partially through the patients' fear of PA. Previous study has con rmed that kinesiophobia is an important mediator of PA in patients with cardiovascular disease 24 . This nding veri ed the FA model.…”
Section: Discussionmentioning
confidence: 88%